2002 IEEE MTT-S International Microwave Symposium Digest (Cat. No.02CH37278)
DOI: 10.1109/mwsym.2002.1012314
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between microstrip lines with finite width ground plane embedded in polyimide layers for 3D-MMICs on Si

Abstract: Abstract--Three-dimenslonal circuits built upon multiple layers of polyimide are required for constructing Si/SiGe monolithic microwave/millimeter-wave integrated circuits on CMOS (low resistivity) Si wafers. Thin film microstrip lines (TFMS) with finite width ground planes embedded in the polyimide are often used. However, the closely spaced TFMS lines are susceptible to high levels of coupling, which degrades circuit performance. In this paper, Finite Difference Time Domain (FDTD) analysis and experimental m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In [22], it was experimentally shown that connecting the two ground planes reduces coupling by 5 dB for a 5000 ~lm long coupled line section. FDTD analysis of 3000 J..lm long coup led lines, which is shown in Fig.…”
Section: Microstrlp Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…In [22], it was experimentally shown that connecting the two ground planes reduces coupling by 5 dB for a 5000 ~lm long coupled line section. FDTD analysis of 3000 J..lm long coup led lines, which is shown in Fig.…”
Section: Microstrlp Characteristicsmentioning
confidence: 99%
“…For example, antenna radiation characteristics are modified by changing the ground plane dimensions of microstrip patch antennas [19]- [21]. Coupling between finite width ground plane microstrip lines embedded in polyimide has been experimentally investigated [22]. However, [22] raised questions about parasitic modes that could not be answered experimentally.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the phase shifts provided by these "true" delay lines are proportional to their dimensions which can be a limiting factor when large phase shifts are required. Attempts to squeeze the unit elements of a meander line may result in a size effective device but also enhances the coupling between adjacent elements [5], [6]. Eventually, if the coupling coefficient is large enough, less delay than expected is observed which can cause false switching of active devices or, on a phased array system, radiation towards unwanted direction.…”
Section: Introductionmentioning
confidence: 99%